Active tuned mass dampers for control of in‐plane vibrations of wind turbine blades. Issue 12 (11th January 2013) - Fitzgerald, B.; Basu, B.; Nielsen, S. R. K.
ABSTRACT: This paper investigates the use of active tuned mass dampers (ATMDs) for the mitigation of in‐plane vibrations in rotating wind turbine blades. The rotating wind turbine blades with tower interaction represent time‐varying dynamical systems with periodically varying mass, stiffness, and damping matrices. The aim of this paper is to determine whether ATMDs could be used to reduce in‐plane blade vibrations in wind turbines with better performance than compared with their passive counterparts. A Euler–Lagrangian wind turbine mathematical model based on energy formulation was developed for this purpose, which considers the structural dynamics of the system and the interaction between in‐plane and out‐of‐plane vibrations. Also, the interaction between the blades and the tower including the tuned mass dampers is considered. The wind turbine with tuned mass dampers was subjected to gravity, centrifugal, and turbulent aerodynamic loadings. Investigations show promising results for the use of ATMDs in the vibration control of wind turbine blades. Copyright © 2013 John Wiley & Sons, Ltd.